Wild fire : a novel - DeMille, Nelson (New York : Warner Books, 2006)
Detective John Corey and wife, FBI agent Kate Mayfield, investigate a plot to detonate nuclear bombs in two American cities, potentially unleashing global chaos.
Keywords: Corey, John (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Nuclear terrorism -- Fiction; Terrorism -- Prevention -- Fiction; Suspense fiction